Optimization of Propylene Glycol and Na CMC in Gel Serum Preparations of Chicken Bone Collagen Antioxidant (Gallus gallus domesticus) - Saputri, Dian; Cahyani, Intan Martha; Kristantri, Rika Sebtiana; Pebriani, Tris Harni; Sari, Wulan Kartika (Journal of Food and Pharmaceutical Sciences, 2025)
One important component found in the dermis layer of the skin is collagen. A decrease in collagen levels can result in reduced skin thickness and strength, loss of elasticity, and decreased skin hydration. Chicken bones serve as a valuable alternative source for the commercial production of collagen, which can be used in easily applicable pharmaceutical preparations, such as gel serum. Antioxidant gel serum preparations are developed by optimizing chicken bone collagen gel serum combined with Na CMC (0-2%) and propylene glycol (8-10%) using the Simplex Lattice Design method, so it is obtained 8 consecutive runs, the comparison is R1 and R3 (1% : 9%), R2 and R8 (2% : 8%), R4 (0,5% : 9,5%), R5 (1,5% : 8,5%) R6 and R7 (0% : 10%). The results indicate that the optimal formula consists of 1.984% Na CMC and 8.016% propylene glycol, yielding a pH of 4.50, a viscosity of 1700 cps, adhesion of 1.72 seconds, spreadability of 6.15 cm, and an IC50 of 57,36 ppm. Validation tests using the T-test demonstrated no significant difference between the observation and prediction results, confirming that the obtained formula was valid.